Implications of the Congregational Dawn Prayer Movement for Achieving the SDGs: A Case Study in Palembang City - Moh. Faizal; Choiriyah; Fadilla; Sondos Jehad Shnewra; Mariam Elbanna; Meriyati (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study investigates the implications of the Congregational Dawn Prayer Movement (Gerakan Subuh Berjamaah) in Palembang City for achieving the Sustainable Development Goals (SDGs), particularly in the context of sustainable human resource development. Theoretical framework: The study is grounded in a theoretical framework of social action theory and Islamic spiritual empowerment, with particular reference to the role of religion in public policy and community development. Literature review: A review of relevant literature highlights the increasing recognition of religious movements as catalysts for holistic development, yet few studies have addressed their direct connection to SDGs. Methods: Employing a qualitative phenomenological approach, this research utilizes participatory observation, in-depth interviews, and documentation as its main data collection techniques. The researcher’s active involvement in the movement provides nuanced insights into its processes and effects. Results: The findings reveal that the Congregational Dawn Prayer Movement, as institutionalized by Palembang Mayor Regulation No. 69 of 2018, extends beyond religious observance. It promotes empowerment across multiple sectors: religious (increased spiritual awareness), social (strengthened community bonds), cultural (revitalization of local Islamic values), economic (micro-business encouragement), political (citizen engagement), and educational (Islamic learning initiatives). Implications: These multidimensional impacts demonstrate how faith-based initiatives can serve as strategic tools for achieving the SDGs, especially in the areas of quality education (SDG 4), reduced inequalities (SDG 10), sustainable communities (SDG 11), and partnerships (SDG 17). Novelty: The novelty of this research lies in its integrative analysis of a religious movement through the lens of the SDGs, emphasizing the transformative potential of Islamic social action within local governance frameworks.